Becoming Nonreligious in a Contemporary Muslim Majority Context: Exploring the Religion to Nonreligion Transition Among Young Adults in Türki̇ye - Başak, Mehmet Ali (Université d'Ottawa / University of Ottawa, 2025)
This dissertation investigates how transformations occur from religious to nonreligious identities, practices, and lifestyles among young adults from Turkish Muslim families. It primarily focuses on the life trajectories of young adults raised in Muslim families within Türkiye's Muslim-majority context. The study addresses several sub-questions, including the meaning and manifestation of nonreligious life in a predominantly Muslim environment, the origins, turning points, and factors influencing disengagement from religion, the role of (non)religious socialization in shaping the shift toward nonreligion, and the differences in attitudes and perceptions toward religion, religiosity, and the social environment between religious and nonreligious individuals. The research employs a mixed-methods approach, drawing on 38 semi-structured, in-depth interviews conducted between July 2022 and October 2023 in seven major cities - each representing the most populous city in its respective region of Türkiye (Istanbul, Ankara, Izmir, Van, Samsun, Gaziantep, and Antalya) - as well as an online survey administered between November 2023 and March 2024 (N = 531). The dissertation's core contributions focus on four primary observations: a) the classification of religious socialization pathways, b) the identification of key push-and-pull factors in religious exits, c) the conceptualization of "hard" and "easy" exits from religiosity and d) the provision of quantitative data that contextualizes the qualitative findings. The life trajectory interviews reveal a range of push-and-pull factors influencing the move away from religion, including perceived injustice, religious pressure, hypocrisy, doubts about textual authenticity, and epistemic skepticism. Significant pull factors are the formation of new social circles, alternative lifestyles, and rationalist worldviews. This study argues that varied forms of (non)religious socialization - observant, moderate, fuzzy, nonreligious, and adverse - shape transition patterns to nonreligion in Türkiye's Muslim-majority context. Based on these socialization categories, it is argued that early childhood experiences of observant and moderate religious socialization tend to produce "hard exits" from religion due to systematic, structured religious upbringing. In contrast, fuzzy and nonreligious socialization more often facilitate gradual, less conflict-ridden pathways out of religiosity.
Keywords: Nonreligion; Religious socialization; Nonreligious Socialization; Religious Exit; Nonreligion in Türkiye; Religious Disengagement; Deconversion; Lived Nonreligion; Religious Transition